Developing a Functional Triticale Noodle by Incorporating Silkworm (Antheraea pernyi and Bombyx mori) Pupae - Yu Liu; Ruixin Liu; Onanong Phuseerit; Hua Li; Sirithon Siriamornpun (Foods, 2025)
To enhance the nutritional and functional properties of triticale noodles, this study assessed their proximate composition, sensory attributes, and antioxidant activity, along with protein and starch digestibilities when supplemented with varying concentrations (0%, 5%, 10%, 15%) of silkworm (Antheraea pernyi and Bombyx mori) pupa powder (SP). Incorporating SP into triticale noodles led to significant enhancements in protein, fat, and ash contents (p < 0.05). The addition of SP may also lead to noticeable color and texture differences by decreasing the lightness (L*) and increasing hardness and springiness in noodles, as well as the flavor difference revealed by E-nose and E-tongue analysis. Furthermore, the total phenolic content and abilities to scavenge DPPH and ABTS radicals improved as the SP level increased. Compared to the control, the SP-fortified noodles had a significantly high in vitro protein digestibility but a low estimated glycemic index. Overall, due to their enhanced nutritional value and bioactivities, SP triticale noodles could be regarded as a healthier alternative to traditional noodles.